Análisis de las técnicas de gestión ambiental de las entidades públicas para enfrentar los problemas ambientales existentes en la provincia de Maynas - región Loreto - 2020 - Sanchez Flores, Sandy Berenise (2023)
The present study was carried out in the province of Maynas, Loreto Region, in order to determine the current state of environmental management techniques in public entities to fase environmental problems in the province of Maynas, Loreto Region. According to the results, the current state of environmental management techniques in public entities to fase environmental problems in the province of Maynas, Loreto Region is related to and has a positive and significant influence on the environmental problems of the región. The chi-square test shows that the research hypothesis is: Environmental Management is related to and has positive and significant influence on regional environmental problems. There are two types of problems that are faced from the Public Sector, one referring to management problems anad the other referring to public problems, based on which the demands of public management are defined. When there is no adequate attention to public problems, it results in the growth of its dimension (its solution becomes larger and more complex.